Metagenomic analysis of the complex microbial consortium associated with cultures of the oil‐rich alga Botryococcus braunii. Issue 4 (28th June 2017) - Sambles, Christine; Moore, Karen; Lux, Thomas M.; Jones, Katy; Littlejohn, George R.; Gouveia, João D.; Aves, Stephen J.; Studholme, David J.; Lee, Rob; Love, John
Abstract: Microalgae are widely viewed as a promising and sustainable source of renewable chemicals and biofuels. Botryococcus braunii synthesizes and secretes significant amounts of long‐chain (C30 ‐C40 ) hydrocarbons that can be subsequently converted into gasoline, diesel, and aviation fuel. B. braunii cultures are not axenic and the effects of co‐cultured microorganisms on B. braunii growth and hydrocarbon yield are important, but sometimes contradictory. To understand the composition of the B. braunii microbial consortium, we used high throughput Illumina sequencing of metagenomic DNA to profile the microbiota within a well established, stable B . braunii culture and characterized the demographic changes in the microcosm following modification to the culture conditions. DNA sequences attributed to B. braunii were present in equal quantities in all treatments, whereas sequences assigned to the associated microbial community were dramatically altered. Bacterial species least affected by treatments, and more robustly associated with the algal cells, included members of Rhizobiales, comprising Bradyrhizobium and Methylobacterium, and representatives of Dyadobacter, Achromobacter and Asticcacaulis . The presence of bacterial species identified by metagenomics was confirmed by additional 16S rDNA analysis of bacterial isolates. Our study demonstrates the advantages of high throughput sequencing and robust metagenomic analyses to define microcosms and further our understanding of microbial ecology. Abstract : Our study demonstrates the advantages of high throughput sequencing and robust metagenomic analyses to characterize the complex microbiota present in cultures of the hydrocarbon‐producing microalga, Botryococcus braunii .